Hired Farmworkers in the US: Demographics, Work Organisation, and Services - Reid, Alison; Schenker, M. (2016)
Objective: Farm work is labor-intensive, physically demanding, and incurs a high risk of injury. The aim of this study was to identify characteristics of farmworkers at increased risk of adverse health outcomes to focus targeted interventions. Methods: The National Agricultural Workers Survey for 2008–2012 was used to compare characteristics associated with adverse health and safety conditions among US-born and Mexican and Central American-born Latino and Indigenous, documented and undocumented farmworkers, separately for males and females. Results: US-born farmworkers had more secure work, worked less onerous tasks, and earned more per hour than other categories of farmworkers. Undocumented Indigenous workers had more precarious work, worked more onerous tasks, and were more likely to do piece work, than undocumented Latino workers. Discussion: We highlight disparities in modifiable occupational health risk factors across groups of farmworkers that are associated with increased risks of work-related injury and poor health.